The transmission of academic values between best friends: How important is an accurate perception?. (4th August 2020) - Reindl, Marion
ABSTRACT: Introduction: Based on the expectancy‐value theory and value transmission theory, the present study investigated the transmission process of academic values between best friends within the classroom. Expectancy‐value theory argues that value related beliefs of important socialization agents influence the development of adolescents' academic values and that this effect is mediated through adolescents' perception of socializers' academic values. In this regard, best friends within the classroom were less focused by researchers although they become important socialization agents in adolescence. Therefore, the present study investigated the influence of friends' actual academic values on adolescents' academic values, and if this effect is mediated through adolescents' perception of friends' actual values. All dimensions of academic values according to the expectancy‐value theory were focused: intrinsic value, attainment value, utility value, and emotional cost. Methods: The research questions were investigated based on a two‐wave longitudinal study in Germany. The final sample comprised of 303 adolescents of the fifth and seventh grade with a stable, reciprocated friend. Results: Structural equation models revealed that the friends' actual attainment value indirectly influenced the attainment value of adolescents through the friends' perceived attainment value. The same effect pattern was found for emotional cost. For the utility value and intrinsic value, no transmission effect was observed. Conclusion: The results provide evidence that the transmission process was not uniform for all of the academic values. Results were discussed in terms of different theoretical concepts explaining the value transmission process between friends.